ألكلام عن البديع : تاريخه وأقسامه - Faqihudin, Didin (State Institute of Islamic Studies (IAIN) Palu, 2007)
This article deals with one aspect of balaghah i.e. badi’. As we know badi’ is a science by which we know some beautiful features of sentences. But how badi’ emerged in the history of Arabic culture? Who is responsible for the rising of badi’? And how many parts badi’ has? This article tries to answer these questions. Kata Kunci : ‘ilm al-badi’,’ilm al-balagah, ‘ilm al-bayan,’ilm al- ma’ani